Corporate activism among impact startups is in good health - O'Sullivan, James (2023)
As younger generations enter the workforce one significant impact they are having is in the growth of corporate activism. Indeed, the corporate activist space has made headlines in recent years for both positive and often spectacularly negative reasons. Companies such as Patagonia have been actively speaking out about various social issues already for decades, yet it has been the recent high-profile missteps by global corporations such as Pepsi and Brewdog – to name but two – that have come to signal a shift in the way the companies interact with their stakeholders and also communicate their values online. In short: an inauthentic attempt at corporate activism will not pass muster in the public court of opinion. Whilst a significant amount of extant literature on the topic looks at the activities of sizeable corporates whose name constitutes half of the term corporate activism itself, this study trains its focus on the other end of the spectrum. Here, too, reside companies that are active in the corporate activist space; startups that by their very impactful nature of their reason for being, exist to speak out about often polemic social issues. This quantitative study specifically looks at a trio of UK-based impact startups in the healthcare arena that are seeking to make an impact on the issue of gender equality. The study positions their corporate activist activities amid their overall social media communications, identifies the communication strategy that they deploy when speaking out publicly about issues and assesses the authenticity of their corporate activism pursuits. Once conclusions have been drawn about the results, the author lists several research proposals that can build upon the fact that this study finds corporate activism among impact startups to be in very good health indeed.